Electrocardiography Predictive Value on Coronary Slow Flow Phenomenon - Erwin Sukandi; Yudhie Tanta; Taufik Indrajaya; Ali Ghanie; Muhammad Irsan Saleh; Irfannuddin; Radiyati Umi Partan; Zulkhair Ali (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Coronary Slow Flow Phenomenon (CSFP) is characterized by the slow flow of contrast in one or more epicardial coronary vessels without evidence of coronary artery stenosis during coronary angiography procedures. CSFP is fairly common at the time of elective angiography with an incidence of around 7% and accounts for about 4% of hospitalized unstable angina cases. Coronary angiography is currently still the only effective way to detect CSFP, but this procedure is an invasive procedure with high costs, there is a risk of allergy to contrast. Electrocardiography (ECG), as a widely available, inexpensive, and simple modality is felt to be an attractive alternative in early detection of this abnormality. The ECG parameters on CSFP discussed in this study include; p-wave dispersion, QT interval dispersion, QRS intrinsic (Tpeak-Tenddeflection duration), and QRS fragmentation. Further studies are needed on the ECG image in CSFP so that in the future ECG can be a cheaper and non-invasive diagnostic modality for CSFP compared to coronary angiography.